Maternal Choline Intake Programs Hypothalamic Energy Regulation and Later‐Life Phenotype of Male Wistar Rat Offspring. Issue 9 (17th March 2020) - Hammoud, Rola; Pannia, Emanuela; Kubant, Ruslan; Liao, Chih‐Sheng; Ho, Mandy; Yang, Neil V.; Chatterjee, Diptendu; Caudill, Marie A.; Malysheva, Olga V.; Pausova, Zdenka; Anderson, G. Harvey
Abstract: Scope: High‐folic‐acid diets during pregnancy result in obesity in the offspring, associated with altered DNA‐methylation of hypothalamic food intake neurons. Like folic acid, the methyl‐donor choline modulates foetal brain development, but its long‐term programing effects on energy regulation remain undefined. This study aims to describe the effect of choline intake during pregnancy on offspring phenotype and hypothalamic energy‐regulatory mechanisms. Methods and results: Wistar rat dams are fed an AIN‐93G diet with recommended choline (RC, 1 g kg −1 diet), low choline (LC, 0.5‐fold), or high choline (HC, 2.5‐fold) during pregnancy. Male pups are terminated at birth and 17 weeks post‐weaning. Brain 1‐carbon metabolites, body weight, food intake, energy expenditure, plasma hormones, and protein expression of hypothalamic neuropeptides are measured. HC pups have higher expression of the orexigenic neuropeptide‐Y neurons at birth, consistent with higher cumulative food intake and body weight gain post‐weaning compared to RC and LC offspring. LC pups have lower leptin receptor expression at birth and lower energy expenditure and activity during adulthood. Conclusion: Choline content of diets that are consumed by rats during pregnancy affects the later‐life phenotype of offspring, associated with altered in utero programing of hypothalamic food intake regulation. Abstract : This study shows that feeding pregnant rats a high‐choline diet leads to higher expression of the hypothalamic appetite‐stimulating neuropeptide Y neurons in male pups at birth and higher food intake and body weight gain during adulthood. A low choline diet results in lower leptin receptor expression at birth and lower activity and energy expenditure during adulthood.